Indonesian Muslim Responses to The Gaza Humanitarian Crisis Since 2023 - Alfredha Shinta Putri; Dewi Masitoh; Hasbi Aswar (Institut Muslim Cendekia, 2026)
This article examines the role of NGOs and Islamic movements in Indonesia, specifically Nahdlatul Ulama (NU), Muhammadiyah, the Indonesian Ulema Council (MUI) and other pro-Palestinian movements in responding to the Gaza genocide since 2023. Utilizing, the concept of NGOs in international politics, this study analyzes three primary dimensions: humanitarian relief, social and economic contribution and political advocacy . Employing a qualitative approach, the research draws on data from online media sources representingvarious Islamic organizations and institutions in Indonesia. The findings demonstrate that Muhammadiyah, NU, and MUI actively support Gaza through integrated humanitarian and political approaches, ranging from official statements, and aid distribution to solidarity actions on social media. However, the study identifies a need for enhanced cross-instittutional coordination and the development of structured and long-term strategies to ensure that Palestinian support agendas are more tangible and impactful. This study contributes to the field of social movements, particularly regarding institutional responses toumanitarian crises.